Gambaran Kepuasan Pasien Berdasarkan Status Akreditasi Di Wilayah Kerja Puskesmas Tabaringan Kota Makassar (Window of Public Health Journal, 2025)
Based on data from the Makassar City Health Office, almost all community health centers (Puskesmas) in Makassar City have been accredited by the Ministry of Health. Tabaringan Community Health Center is one of the health facilities that has received basic accreditation. Some complaints frequently conveyed by patients at this community health center relate to the unfriendly attitude of staff, slow service response, and limited information regarding drug use. This study aims to describe the level of patient satisfaction based on the community health center accreditation status, reviewed from various dimensions of service quality. The type of research used is quantitative with a descriptive approach. Sampling was carried out using purposive sampling with a total of 227 respondents. Data collection used a questionnaire, then analyzed univariately to determine the frequency distribution of each variable. The results of the study showed an increase in patient satisfaction after accreditation was implemented. In the Tangibles dimension, before accreditation, 49.3% of patients were quite satisfied and 50.7% were dissatisfied, while after accreditation, this increased to 89.4% were quite satisfied and only 10.6% were dissatisfied. In the Reliability dimension, prior to accreditation, 89.4% of patients reported being quite satisfied, while 10.6% were less satisfied. After accreditation, this increased to 99.6% quite satisfied and 0.4% less satisfied. The Responsiveness dimension showed that before accreditation all respondents (100%) felt quite satisfied, and after accreditation, 99.6% remained quite satisfied with 0.4% stating less satisfied. Meanwhile, in the Assurance dimension, before accreditation, only 1.3% were quite satisfied, and 98.7% were less satisfied. However, after accreditation, there was a significant increase, with 89.4% being quite satisfied and 10.6% less satisfied. The researcher emphasizes the need for further research to conduct a more in-depth analysis of the factors that influence patient satisfaction levels based on the accreditation status of community health centers, and invites the audience to participate in this important endeavor.